Korelasi Keterampilan Membaca Pemahaman dengan Keterampilan Mengapresiasi Cerpen pada Siswa Sekolah Dasar - Wa Ode Zuhroh Ilmiah; Munirah; Abdan Syakur (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
Reading is a very important factor in the world of literacy because the benefits are very large. Thus, reading is one of the benchmarks for a person's level of intelligence. Likewise, the influence of reading on the appreciation of literary works, in this case, short stories. This study aims to determine the correlation between reading comprehension and appreciation of short stories for fifth-grade students at SDN Antapia, Wakatobi Regency. This research is a correlational study. The research sample amounted to 10 people with the saturated sampling method. Data collection techniques using test instruments. The data analysis technique used is statistical-descriptive analysis. The results obtained from the research have a correlation coefficient rcount of 0.931, which is greater than 0.05. That is, there is a positive relationship or correlation between the variable reading comprehension and the variable appreciating short stories in fifth-grade students of SDN Antapia, Wakatobi Regency and the degree of correlation between variables is very large. Thus, it can be concluded that the higher the student's ability to read, the higher the level of appreciation of short stories.